2015
DOI: 10.1250/ast.36.139
|View full text |Cite
|
Sign up to set email alerts
|

100-MHz ultrasonic linear array transducers based on polyurea-film

Abstract: Eight-and 32-element ultrasonic array transducers using polyurea films are fabricated and experimentally tested in this study. Aromatic polyurea thin films, prepared by vapor deposition polymerization, are suitable for use as an ultrasonic transducer. In this paper, we present two types of polyurea array transducer with 20 and 200 mm pitches. The polyurea films were prepared through vapor deposition polymerization, and miniature electrode arrays were fabricated by a lithographic technique. Resonance frequencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Qiu et al [ 4 ] discussed fabrication, electrical integration, and electrical and acoustic measurements of PMUT arrays for sensing, actuation and imaging. Nakazawa et al [ 5 ] fabricated eight-element, 200 µm pitch and 32-element, 20-µm pitch, 1D arrays based on a polyurea film, and experimentally measured the resonance frequencies at 30 MHz, 65 MHz, and 100 MHz. Cheng et al [ 6 ] reported a 2D PMUT array consisting of 20 diaphragms, with each diaphragm having 60 µm diameter, and showed its resonance frequency at 8 MHz with 62.5% bandwidth.…”
Section: Introductionmentioning
confidence: 99%
“…Qiu et al [ 4 ] discussed fabrication, electrical integration, and electrical and acoustic measurements of PMUT arrays for sensing, actuation and imaging. Nakazawa et al [ 5 ] fabricated eight-element, 200 µm pitch and 32-element, 20-µm pitch, 1D arrays based on a polyurea film, and experimentally measured the resonance frequencies at 30 MHz, 65 MHz, and 100 MHz. Cheng et al [ 6 ] reported a 2D PMUT array consisting of 20 diaphragms, with each diaphragm having 60 µm diameter, and showed its resonance frequency at 8 MHz with 62.5% bandwidth.…”
Section: Introductionmentioning
confidence: 99%